Performance analysis of adaptive channel coding with OFDM modulation over Rayleigh fading channels - Venkatesan Sangeetha; Pattipati Naga Sudha (Bulletin of Electrical Engineering and Informatics, 2026)
In the contemporary wireless communication system, the orthogonal frequency division multiplexing (OFDM) in conjunction with the use of the error correction code scheme is important towards ensuring a reliable transmission of data through the fading channel. This work is a complete analysis of performance of OFDM modulation combined with adaptive channel coding schemes are low-density parity check (LDPC), turbo, and convolutional code while using the Rayleigh fading channel. Error correction schemes such as LDPC, turbo, and convolutional code are used with a variety of trade-offs on their error correction performance. The system is coded in MATLAB/Simulink and run with 64 subcarriers, a length of cyclic prefix of 16 and a 16-quadrature amplitude modulation (16-QAM) modulation, channel coding techniques which are preferred upon the levels of signal-to-noise ratio (SNR) between 0 to 20 dB and the level of performance is measured by bit error rate (BER). The simulation findings prove that LDPC code achieves the highest performance at high SNR values, convolutional code has moderate BER at mid-SNR range, and turbo code has superior performance at low-SNR range and outperforming both LDPC and convolutional codes. These findings indicate that adaptive channel coding in the OFDM system is effective over Rayleigh fading.